Why Virtue Is not Quite Enough: Descartes on Attaining Happiness - Viljanen Valtteri (De Gruyter Open Ltd, 2025)
Descartes explicitly states that virtue is sufficient for attaining happiness. In this paper I argue that, within the framework he develops, this is not exactly true: more than virtuous action is needed to secure happiness. I begin by analyzing, in Section 2, the Cartesian notion of virtue in order to show the way in which it closely connects to what, for Descartes, forms the very essence of morality – the correct use of our free will. Section 3, in turn, discusses Descartes’s view of happiness and its relation to the highest good. Thereby is laid the foundation for Section 4, which offers a reconstruction of the argument that virtue leads to happiness. Section 5 concludes the discussion by suggesting how and why Descartes leaves a crucial premise – an intellectual insight that consists of three main elements – unmentioned when he claims that virtue is sufficient for happiness.